SARS-CoV-2 samples may escape detection because of a single point mutation in the N gene - Ziegler, Katharina; Steininger, Philipp; Ziegler, Renate; Steinmann, Jörg; Korn, Klaus; Enßer, Armin (Eurosurveillance, 2020)
We found that a single nucleotide polymorphism (SNP) in the nucleoprotein gene of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from a patient interfered with detection in a widely used commercial assay. Some 0.2% of the isolates in the EpiCoV database contain this SNP. Although SARS-CoV-2 was still detected by the other probe in the assay, this underlines the necessity of targeting two independent essential regions of a pathogen for reliable detection.
CRIS-Team Scopus Importer:2020-10-23